Low‐Protein Diets with Fixed Carbohydrate Content Promote Hyperphagia and Sympathetically Mediated Increase in Energy Expenditure. Issue 21 (7th August 2019) - Zapata, Rizaldy C.; Singh, Arashdeep; Pezeshki, Adel; Avirineni, Bharath S.; Patra, Souvik; Chelikani, Prasanth K.
Abstract : Scope: Dietary protein restriction elicits hyperphagia and increases energy expenditure; however, less is known of whether these responses are a consequence of increasing carbohydrate content. The effects of protein‐diluted diets with fixed carbohydrate content on energy balance, hormones, and key markers of protein sensing and thermogenesis in tissues are determined. Methods and results: Obesity‐prone rats ( n = 13–16 per group) are randomized to diets containing fixed carbohydrate (52% calories) and varying protein concentrations: 15% (control), 10% (mild protein restriction), 5% (moderate protein restriction) or 1% (severe protein restriction) protein calories, or protein‐matched to 5% protein, for 21 days. Propranolol and ondansetron are administered to interrogate the roles of sympathetic and serotonergic systems, respectively, in diet‐induced changes in energy expenditure. It is found that mild‐to‐moderate protein restriction promotes transient hyperphagia, whereas severe protein restriction induces hypophagia, with alterations in meal patterns. Protein restriction enhances energy expenditure that is partly attenuated by propranolol, but not ondansetron. Moderate to severe protein restriction decreases gains in body weight, lean and fat mass, decreased postprandial glucose and leptin, but increased fibroblast growth factor‐21 concentrations. Protein‐matching retains lean mass suggesting that intake of dietary protein, but not calories, is important for preserving lean mass. Notably, protein restriction increases the protein and/or transcript abundance of key amino acid sensing molecules in liver and intestine (PERK, eIF2α, ATF2, CHOP, 4EBP1, FGF21), and upregulated thermogenic markers (β2AR, Klotho, HADH, UCP‐1) in brown adipose tissue. Conclusion: Low‐protein diets promote hyperphagia and sympathetically mediated increase in energy expenditure, prevent gains in tissue reserves, and concurrently upregulate hepatic and intestinal amino acid sensing intermediaries and thermogenic markers in brown adipose tissue. Abstract : Mild‐to‐moderate reduction of protein in the diet of rats, but at fixed carbohydrate content, increases food consumption and burning off calories. Interestingly, moderate‐to‐severe reduction of dietary protein decreases body weight, fat, and lean mass, and activates important molecules that sense amino acids in the gut and liver, molecules that increase calorie burning in brown fat tissue.